2009
DOI: 10.1007/s10856-009-3796-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antibacterial silver coated yarns

Abstract: Surface treatments of textile fibers and fabrics significantly increase their performances for specific biomedical applications. Nowadays, silver is the most used antibacterial agent with a number of advantages. Among them, it is worth to note the high degree of biocompatibility, an excellent resistance to sterilization conditions, antibacterial properties with respect to different bacteria associated with a long-term of antibacterial efficiency. However, there are only a few antibacterial fibres available, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 18 publications
5
71
0
1
Order By: Relevance
“…One approach is to provide the polymer with antimicrobial properties in an "offline" preparation process. In this case, the thread is superficially coated using a specific antimicrobial component previously dissolved in a solvent (Blaker et al 2004;Dubas et al 2011;Harnet et al 2009;Gupta et al 2007Gupta et al , 2008Pollini et al 2009;Saxena et al 2011;Zurita et al 2006). Another approach is to add the biocide agent in the polymers "online", i.e.…”
Section: Introductionmentioning
confidence: 99%
“…One approach is to provide the polymer with antimicrobial properties in an "offline" preparation process. In this case, the thread is superficially coated using a specific antimicrobial component previously dissolved in a solvent (Blaker et al 2004;Dubas et al 2011;Harnet et al 2009;Gupta et al 2007Gupta et al , 2008Pollini et al 2009;Saxena et al 2011;Zurita et al 2006). Another approach is to add the biocide agent in the polymers "online", i.e.…”
Section: Introductionmentioning
confidence: 99%
“…According to the standard antibacterial test "SNV 195920-1992", specimens showing more than 1 mm microbial zone inhibition can be considered as good antibacterial agents [69]. In the present study since the NCS/SA/MC film prepared in all ratios shows the inhibitory zone greater than 1 mm it was concluded that NCS/SA/MC film prepared in 4:16:1 ratio acts as good antibacterial agent and effective in killing the microbes.…”
Section: Antibacterial Activitymentioning
confidence: 46%
“…Powdered titanium dioxide is also commonly used as a whitener in toothpastes [15]. Moreover, nanoparticles can be used successfully in other materials, including hydrogels [14,15,16]. Chladek et al presented a method for incorporating NAg into chemically cured silicone soft-liner materials.…”
Section: Denture Stomatitismentioning
confidence: 99%